6(3+n)=5(n+1)

Simple and best practice solution for 6(3+n)=5(n+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3+n)=5(n+1) equation:


6(3+n)=5(n+1)

We simplify the equation to the form, which is simple to understand
6(3+n)=5(n+1)

Reorder the terms in parentheses
+(+18+6n)=5*(n+1)

Remove unnecessary parentheses
+18+6n=+5+*(+n+1+)

Reorder the terms in parentheses
+18+6n=+(+5n+5)

Remove unnecessary parentheses
+18+6n=+5n+5

We move all terms containing n to the left and all other terms to the right.
+6n-5n=+5-18

We simplify left and right side of the equation.
+1n=-13

We divide both sides of the equation by 1 to get n.
n=-13

See similar equations:

| 12x^2+xy+6y^2=0 | | 7x^3-2x^4+45x^2-184x=-80 | | 2y+17y=114 | | 1250=1000+25(x) | | 19m=16-13m | | x/17=-5 | | 5a+3(216-a)=888 | | -9.3x=46.5 | | 784=4*f | | 21a^2+11a-2=0 | | -7(4b+4)+(29b-4)=0 | | 2.4q-2.5-4.4q=-3q-5.5 | | X-18=-x^2+2 | | 12x+a=4(3x-8) | | 1550=1000+25(x) | | n+9=m | | 2x-2=-3x-3 | | -21+25n=25 | | 1250=700+85(x) | | -x+10x=72 | | 6(4x-1)=2(12x+3) | | 7(m-5)=15(3-m)+2m | | 1550=700+85(x) | | 1500=700+85(x) | | y-30=-25 | | 15x^2-66x+24=0 | | y=1000+25(10) | | 11-2x=5(x-5)+15 | | 28x^3-39x^2+12x-1=0 | | 9+5s-2=7-2s | | 2L-6=12-L | | x+(x+1)=77 |

Equations solver categories